Intestinal cell-specific vitamin D receptor (VDR)-mediated transcriptional regulation of CYP3A4 gene - Pavek, Petr; Pospechova, Katerina; Svecova, Lucie; Syrova, Zdenka; Stejskalova, Lucie; Blazkova, Jana; Dvorak, Zdenek; Blahos, Jaroslav (Biochemical pharmacology, 2010)
CYP3A4 is the most important drug-metabolizing enzyme that is involved in biotransformation of more than 50% of drugs. Pregnane X receptor (PXR) dominantly controls CYP3A4 inducibility in the liver, whereas vitamin D receptor (VDR) transactivates CYP3A4 in the intestine by secondary bile acids. Four major functional PXR-binding response elements of CYP3A4 have been discovered and their cooperation was found to be crucial for maximal up-regulation of the gene in hepatocytes. VDR and PXR recognize similar response element motifs and share DR3(XREM) and proximal ER6 (prER6) response elements of the CYP3A4 gene. In this work, we tested whether the recently discovered PXR response elements DR4(eNR3A4) in the XREM module and the distal ER6 element in the CLEM4 module (CLEM4-ER6) bind VDR/RXRalpha heterodimer, whether the elements are involved in the intestinal transactivation, and whether their cooperation with other elements is essential for maximal intestinal expression of CYP3A4. Employing a series of gene reporter plasmids with various combinations of response element mutations transiently transfected into four intestinal cell lines, electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation assay (ChIP), we found that the CLEM4-ER6 motif interacts with VDR/RXRalpha heterodimer and partially cooperates with DR3(XREM) and prER6 in both basal and VDR-mediated inducible CYP3A4 regulation in intestinal cells. In contrast, eNR3A4 is involved only in the basal transactivation in intestinal cells and in the PXR-mediated rifampicin-induced transactivation of CYP3A4 in LS174T intestinal cells. We thus describe a specific ligand-induced VDR-mediated transactivation of the CYP3A4 gene in intestinal cells that differs from PXR-mediated CYP3A4 regulation in hepatocytes.
Keywords: Intestinal Mucosa; Cytochrome P-450 CYP3A; Chromatin Immunoprecipitation; Gene Expression Regulation, Enzymologic; Base Sequence; Intestines; regulace genové exprese enzymů; Cell Line, Tumor; chromatinová imunoprecipitace; retardační test; Transcription, Genetic; lidé; cytochrom P-450 CYP3A; DNA primery; polymerázová řetězová reakce s reverzní transkripcí; Receptors, Calcitriol; střeva; genetická transkripce; Reverse Transcriptase Polymerase Chain Reaction; sekvence nukleotidů; DNA Primers; Electrophoretic Mobility Shift Assay; receptory kalcitriolu; nádorové buněčné linie; střevní sliznice; Humans